UTAUT Analysis of E-learning Users: A Case Study at ABC University - Go, Ratna Yulika; Prabowo, Ary; Hidayah, Qori Halimatul (Universitas Nusa Cendana, 2025)
The concept of e-learning has been adapted and used in Indonesia since the 1940s, and its development has continued to progress to this day. The COVID-19 pandemic has led to more comprehensive use of elearning. Unfortunately, ABC University was not prepared for the drastic shift to fully online learning, and its e-learning system is not yet integrated with the academic information system (SIAKAD). Other challenges include system bugs and a lack of optimization in discussion forums. As a result, students and lecturers are not able to use e-learning to its full potential. To identify the root causes of these issues, this study aims to determine the influencing factors of e-learning usage at ABC University, with the findings intended to provide recommendations for the university to address the challenges it faces. The study uses a mixed-method approach, combining quantitative and qualitative methods to process and validate the data. The UTAUT (Unified Theory of Acceptance and Use of Technology) approach is applied to identify the factors that affect e-learning usage, with analysis conducted using PLS SEM (Partial Least Squares Structural Equation Modeling). The study results show that among the five factors examined—Performance Expectancy (PE), Effort Expectancy (EE), Social Influence (SI), Facilitating Conditions (FC), and Behavioral Intention (BI)—only Social Influence (SI) significantly impacts e-learning usage, while the other four factors do not have a significant effect. The recommendations from this study include the need for system integration between e-learning and SIAKAD to ensure optimal use, as well as conducting maintenance every three months, facilitating meeting accounts, and adding audio-video features in discussion forums.